Public Relations Practice in Nigeria’s Corruption-Ridden Environment - Thomas Okechukwu; Linus Ogbuoshi; Ferdinand Obasi (ESUT JOURNAL OF SOCIAL SCIENCES, 2025)
This article discussed public relations practice in Nigeria’s corruption-ridden environment: challenges and prospects, and specifically identified the functions and objectives of public relations, highlighted the extent corruption has characterized the socio-economic and political environment of Nigeria, and discussed some of the challenges facing public relations practice in Nigeria and pointed out how the challenges could be overcome. The theoretical framework of this article was anchored on the excellent theory which resulted from a study about the best practice in public relation. In the article, write-ups from available relevant literature were considered and used to analyse public relations practice in Nigeria’s corruption-filled environment, and discuss the challenges and prospects of public relations practice. In the conclusion, it was noted that truly, corruption is evident in the Nigerian socio-economic and political environment and it posses challenges to the practice of public relations. Nevertheless, ways to overcome the challenges were pointed out and all concerned were encouraged to follow the steps as public relations practice in Nigeria has great prospect to flourish.